Kapitalisasi Pendidikan: Dampak Positif dan Negatif terhadap Pendidikan Islam - Sefti Triani; Qolbi Khoiri (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
Abstract This study discusses the phenomenon of educational capitalization and its impact on Islamic education. Educational capitalization is defined as the process of implementing market economic principles, such as competition, profitability, and privatization, which have a significant impact on the education system. In this context, education is viewed as a market where a commercial approach is applied in the management, financing, and provision of educational services. This study aims to identify the positive and negative impacts of educational capitalization on Islamic educational institutions, as well as to review Islamic views on educational capitalization. The method used is a literature study with a descriptive analytical approach to various library sources. The results of the study indicate that educational capitalization has a positive impact in the form of increasing institutional autonomy, innovation, and accelerating the development of science and technology. However, on the other hand, it also has negative impacts such as excessive commercialization, privatization, increasing education costs, and threats to the fundamental values ??of Islamic education. The conclusion of this study emphasizes the importance of regulation and strengthening Islamic values ??to minimize the negative impacts of educational capitalization. Keywords: Islamic educational capitalization, positive impact, negative impact Abstrak Penelitian ini membahas fenomena kapitalisasi pendidikan dan dampaknya terhadap pendidikan Islam. Kapitalisasi pendidikan diartikan sebagai proses penerapan prinsip-prinsip ekonomi pasar, seperti persaingan, profitabilitas, dan privatisasi, yang berpengaruh signifikan terhadap sistem pendidikan. Dalam konteks ini, pendidikan dipandang sebagai pasar di mana pendekatan komersial yang diterapkan dalam pengelolaan, pembiayaan, dan penyediaan layanan pendidikan. Penelitian ini bertujuan untuk mengidentifikasi dampak positif dan negatif kapitalisasi pendidikan terhadap lembaga pendidikan Islam, serta mengulas pandangan Islam terhadap kapitalisasi pendidikan. Metode yang digunakan adalah studi literatur dengan pendekatan deskriptif analitis terhadap berbagai sumber pustaka. Hasil penelitian menunjukkan bahwa kapitalisasi pendidikan memberikan dampak positif berupa peningkatan otonomi kelembagaan, inovasi, dan percepatan pengembangan ilmu pengetahuan serta teknologi. Namun, di sisi lain juga menimbulkan dampak negatif seperti komersialisasi berlebihan, privatisasi, peningkatan biaya pendidikan, serta ancaman terhadap nilai-nilai fundamental pendidikan Islam. Kesimpulan penelitian ini menekankan pentingnya regulasi dan penguatan nilai-nilai keislaman untuk meminimalkan dampak negatif kapitalisasi pendidikan. Kata kunci: kapitalisas pendidikan Islam, dampak positif, dampak negatif